Homogenization at ultra-high pressure (UHPH): Effects on milk and applications in cheese manufacture - Mayta-Hancco, Jhony (2020)
Ultra-high-pressure homogenization (UHPH) is an emerging technology with applications in fluid processing. Although, this technology is based on the same principles of conventional homogenizers, the new designs and use of valve construction materials have made it possible to reach pressures of 350 to 400 MPa. The advantages of UHPH include the reduction of the particle size, an increase in the useful life through the inactivation of microorganisms and improvements in functionality due to the increase in the capacity and stability of the emulsion, with minimal effects on the nutritional value and sensory characteristics. Also, the thermal effects are less due to the treatment time (less than one second). UHPH technology is a sustainable process that has a potential application in the cosmetic, pharmaceutical and dairy industries. This review shows an overview of some recent studies of the application of UHPH technology in milk treatment and cheese manufacturing.